AVALIAR A ILUMINAÇÃO ARTIFICIAL NOS CENTROS CIRÚRGICOS EM CUIABÁ: ESTUDO DE CASO - Romani, Tula Kirst; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707708 To ensure safety in surgery, in addition to all the technical elements of the procedureitself, it is necessary that the conditions of the place where it happens to be the best possible inorder to reduce the variables that can alter the outcome of the procedures, increase the level ofsuccess and preserve the health of professionals working within the surgical center. This articleaims to point out the general importance of proper lighting in this sector of the hospital and thetasks it developed specific objectives were to make a profile of this hospital for two health-carefacilities at two different times of the year in Cuiabá, check your respect rules that dictate the minimum values for ambient lighting in the operating room and even check for change in theprofile of lighting environments between dry and wet periods of the year. Data were collectedthrough observation of the physical environment and equipment available to these professionalsto brighten your desktop and battery of measurements of luminance levels of the operatingrooms. The criteria for data analysis were the NBR 5413 (1992) which determines the minimumluminance for environments, and recommendations for lighting installations in the healthcare ofIESNA (American Society for Engineering Lighting). The popular surgical centers need adjustmentsbecause not fully met any of the criteria used in the survey. The luminance levels are below theminimum values set by NBR 5413 (1992) in all periods in which measurements were taken, andthe lighting equipment do not conform with the recommendations of IESNA.